2018
DOI: 10.1111/jph.12696
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Sydowia polyspora and its pathogenicity on Pinus yunnanensis in Southwestern China

Abstract: Sydowia polyspora occurs often as an epiphyte or endophyte of conifers and is widely distributed around the world. It is also reported as a fungus associated with bark beetles. In this study, based on ITS sequence data and morphological characteristics, 14 strains collected from the beetle bodies and galleries of Tomicus minor and Tomicus yunnanensis infesting Pinus yunnanensis in Southwestern China were identified as S. polyspora. To assess the virulence of S. polyspora to P. yunnanensis, pathogenicity tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 37 publications
2
32
1
Order By: Relevance
“…Two of the three isolates used in the inoculation tests did not cause necrosis on the shoots. Pan et al () also verified different degrees of symptoms development on needles of P. yunannensis inoculated with different S. polyspora strains, when four of the ten strains tested caused no symptoms. In addition, Talgø et al () verified no symptom development in one of the three tests performed with the same strains, thus, suggesting that diverse abiotic and biotic factors can play an important role in the development of the disease, either by affecting the ecology of the pathogen or the susceptibility of the host.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Two of the three isolates used in the inoculation tests did not cause necrosis on the shoots. Pan et al () also verified different degrees of symptoms development on needles of P. yunannensis inoculated with different S. polyspora strains, when four of the ten strains tested caused no symptoms. In addition, Talgø et al () verified no symptom development in one of the three tests performed with the same strains, thus, suggesting that diverse abiotic and biotic factors can play an important role in the development of the disease, either by affecting the ecology of the pathogen or the susceptibility of the host.…”
Section: Resultsmentioning
confidence: 85%
“…In order to test the pathogenicity of S. polyspora isolates on stone pine, inoculation was performed following a method based on Pan et al (). Three isolates, from different geographic origins, were randomly selected (MEAN1029, MEAN1030, MEAN1031).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…across Europe and North America [90][91][92], necrosis on shoots of Pinus pinea L. [93] as well as necrosis on stems and needles on Pinus yunnanensis Franch. [94]. Cleary et al [24] suggested that this endophyte is opportunistic pathogen, that due changes in climate can potentially increase its pathogenicity.…”
Section: Main Species Of Pinus Twigsmentioning
confidence: 99%
“…Isolate morphology was assessed after 6 and 15 days of growth on PDA medium at 25 • C under the 12 h photoperiod. Anamorph characteristics, including the size and shape of conidiophores and conidia, were observed in water on a glass slide using an Olympus compound microscope (BX 53; Dongguan Yijiang Instrument Co. Ltd., Guangdong, China) [37]. Measurements of 50 conidia, including length and width, and 95% confidence intervals together with extreme values were determined [24].…”
Section: Morphological Identificationmentioning
confidence: 99%